DIGITAL APPLICATIONS FOR COMMUNITY EMPOWERMENT: ANALYSIS OF OPPORTUNITIES AND CHALLENGES IN ULU BELU DISTRICT, TANGGAMUS REGENCY - Jasmadi, Jasmadi; Maryam, Dewi; Salim, Agus; Zaimuddin AS, Lutfi; Setiawati, Rini; Jauhari, Tontowi (JURNAL AL-IJTIMAIYYAH, 2024)
In the era of digital technology, inclusive communication is important so that the empowerment process can reach all levels of society, including marginalized groups that are often overlooked due to the digital divide. This research aims to analyze the implementation of digital applications in community empowerment in the villages of Ulubelu District, Tanggamus Regency, focusing on the challenges, opportunities, and obstacles faced. This research uses a qualitative approach with a case study design and data obtained through in-depth interviews, participatory observation, and document analysis. Data mining was conducted with community leaders, village government, and local people. The results showed that infrastructure barriers, such as inaccessible roads and lack of internet signal, are the main obstacles in optimizing the use of digital applications, such as the Village Information System (SID), SIKS-NG, and other development planning applications. Villages such as Sinar Banten, Rejosari, Ulu Semong, and Petay Kayu face issues related to the accessibility of digital technology and information. In addition, a lack of digital literacy among the community, especially the elderly, and limited training for village officials exacerbate the situation. However, digital applications also have the potential to support transparency, efficiency, and access to information in community empowerment programs with improved technology infrastructure and inclusive digital literacy training. This study reveals the importance of collaboration between the government, village apparatus, and communities in designing sustainable digitalization strategies. This research enriches the literature related to digitalization in rural areas and provides practical recommendations to overcome barriers to technology implementation. The results are expected to serve as a reference for policymakers and practitioners to develop a more inclusive approach in supporting digital-based community empowerment in remote areas.